Epidemiology of alcohol consumption and related problems in Latin American countries: Contributions of psychology - Cremonte, Mariana (2018)
Alcohol consumption is the leading risk factor for morbi-mortality in many Latin American Countries. However, epidemiologic studies are relatively scarce. Among factors such as limited research capacity, disciplinary traditions and an emphasis on psychopathology within the field of psychology, have been postulated to account for this. The aim of this article is to review epidemiologic research on alcohol in Spanish Speaking Latin American Countries, and to measure the contribution of psychology to the field. A systematic search was performed in English and Spanish using regional and international data bases. We identified 269 articles. Most focused on consumption patterns in youth, with samples from a single school and using a variety of measures. With the exception of multinational efforts like Emergency Room Collaborative Alcohol Analysis Project or those supported by World Health Organization/Pan American Health Organization, studies reviewed reflected little cross country collaboration. Mexico accounted for most of the productivity, while many countries had very few or no articles. Most research was performed by health science researchers with a small contribution from psychology, but which increased significantly over time. The results of this review provide a broad identification of patterns regarding epidemiologic research on alcohol, and demonstrate the need for national scientific policies to promote research on public health topics.